Association between Mangrove Types and Some Mangrove Crab Species in West Lombok Sheet Mangrove Ecosystem - Jurlia Apriliani Tonti Riska; Abdul Syukur; Lalu Zulkifli (Postgraduate, University of Mataram, 2023)
One of the ecosystems found in coastal areas is the mangrove ecosystem. Mangroves have many functions including as a shelter, a place to find food, a breeding ground for aquatic biota. Damage to mangrove areas can cause a decrease in the quality of mangrove ecosystems, especially for the life of mangrove crabs. Mud crab is one of the aquatic biota associated with mangroves and its life is influenced by the presence of mangrove forests. Therefore, the purpose of this study was to determine the diversity of mud crabs that live in mangrove ecosystems and the association of mangrove species with several species of mud crabs in the coastal mangrove ecosystem of Lembar, West Lombok. Mud crab samples were taken using purposive sampling by looking at the density of mangroves in each observation plot. The collected data were analyzed by diversity index, ecological index, association and Pearson's correlation coefficient. Then a simple linear regression analysis was performed with the variable (x) density of mangroves and (y) density of mangrove crabs. The results of this study were found to be 10 species of mud crabs consisting of 2 families of Ovalipidae and 8 families of Portunidae which belong to the moderate diversity index. There were 2 species of mud crabs that were positively associated with 2 species of mangroves out of 10 species of mud crabs found. Linear regression equation y = 0.2482x + 0.0004 with a pearson correlation coefficient (rÂ²) (0.58). The conclusion of this study is that there is a relationship between mangrove density and mangrove crab densityOne of the ecosystems found in coastal areas is the mangrove ecosystem. Mangroves have many functions including as a shelter, a place to find food, a breeding ground for aquatic biota. Damage to mangrove areas can cause a decrease in the quality of mangrove ecosystems, especially for the life of mangrove crabs. Mud crab is one of the aquatic biota associated with mangroves and its life is influenced by the presence of mangrove forests. Therefore, the purpose of this study was to determine the diversity of mud crabs that live in mangrove ecosystems and the association of mangrove species with several species of mud crabs in the coastal mangrove ecosystem of Lembar, West Lombok. Mud crab samples were taken using purposive sampling by looking at the density of mangroves in each observation plot. The collected data were analyzed by diversity index, ecological index, association and Pearson's correlation coefficient. Then a simple linear regression analysis was performed with the variable (x) density of mangroves and (y) density of mangrove crabs. The results of this study were found to be 10 species of mud crabs consisting of 2 families of Ovalipidae and 8 families of Portunidae which belong to the moderate diversity index. There were 2 species of mud crabs that were positively associated with 2 species of mangroves out of 10 species of mud crabs found. Linear regression equation y = 0.2482x + 0.0004 with a pearson correlation coefficient (rÂ²) (0.58). The conclusion of this study is that there is a relationship between mangrove density and mangrove crab density